Comparative cephalometric study for the anteroposterior diagnosis of the apical bases between the angles ANB and the projection USP. - Marengo Castillo, Héctor (2006)
A comparative cephalometric study was conducted among 218 children from 7 to 12 years of both sexes who attended the Integral clinic of children at San Marcos National University among the years 1998-2003. The children had the firsts permanent molars and central incisors in mouth and had not received orthodontic treatment. To know the coincidence or not in the diagnosis of the sagital malocclusion , a comparative analysis was made between The angle ANB and the projection USP; Kappa’s statistical test was applied to their results to determinate the existence of concordance between the analysis by their evaluation scale. The result shows a low level of concordance between the angle ANB and the PROJ USP (Kappa indices 0,359). The higher concordance was diagnostic in class II children (115 cases). Nineteen children were diagnostic class III according to the PROJ USP and 1 according to the angle ANB , from these, only in open case was found concordance. The majority of cases diagnostic as class II according to PROJ USP were diagnostic as class I according to the angle ANB.